Integrating Liquid Probiotics into Sustainable Poultry Systems to Enhance Egg Protein Content in Gallus sp. - Nurul Magfirah Sukri; Eddy Soekendarsi; Zaraswati Dwyana; Herlina Rante (Indonesian Journal of Ecology and Conservation, 2025)
The sustainability of livestock ecosystems increasingly depends on improving feed conversion efficiency and reducing reliance on synthetic chemical additives. Probiotics offer a biological alternative to enhance poultry productivity while maintaining ecological balance. This study aims to evaluate the enhancement of egg protein content in laying hens (Gallus sp.) through the integration of liquid probiotics into sustainable poultry systems. The research followed a Completely Randomized Design (CRD) with three treatments: control (M0), liquid probiotic culture (M1), and commercial probiotic (M2). Egg protein content was analyzed using the Kjeldahl method, involving digestion, distillation, and titration to determine total nitrogen levels, which were converted into crude protein percentages. The findings indicate that while liquid probiotic integration showed a positive trend in enhancing egg protein levels, the statistical analysis revealed no significant difference (P>0.05) among treatments. The liquid probiotic culture (M1) yielded the highest mean protein content at 11.26 ± 1.361 mg/g, compared to the control group (10.5 ± 1.371 mg/g). This numerical improvement suggests that probiotics support gut microflora health, potentially aiding nitrogen metabolism efficiency. Although not statistically significant in this trial, the implementation of probiotics in sustainable livestock systems supports ecosystem conservation by providing a chemical-free alternative for poultry management and promoting long-term biological resilience